2020
DOI: 10.21203/rs.3.rs-56955/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal Prediction of COVID-19 Mortality and Risk Assessment

Abstract: This paper presents a multivariate functional data statistical approach, for spatiotemporal prediction of COVID-19 mortality counts. Specifically, spatial heterogeneous nonlinear parametric functional regression trend model fitting is first implemented. Classical and Bayesian infinite-dimensional log-Gaussian linear residual correlation analysis is then applied. The nonlinear regression predictor of the mortality risk is combined with the plug-in predictor of the multiplicative error term. An empirical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example, Giuliani et al (2020) have used GLM to predict COVID-19 infections in regions of Italy, and found the spatial interactions of nearby places to have a high influence on modeling; this shows the importance of accounting for the spatial effects explicitly. In a parallel vein, Bayesian modeling methods have also been used in this epidemiological context (Aswi et al 2019;Song et al 2019;Torres-Signes et al 2020;Gelman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Giuliani et al (2020) have used GLM to predict COVID-19 infections in regions of Italy, and found the spatial interactions of nearby places to have a high influence on modeling; this shows the importance of accounting for the spatial effects explicitly. In a parallel vein, Bayesian modeling methods have also been used in this epidemiological context (Aswi et al 2019;Song et al 2019;Torres-Signes et al 2020;Gelman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Giuliani et al (2020) have used GLM to predict COVID-19 infections in regions of Italy, and found the spatial interactions of nearby places to have a high influence on modeling; this shows the importance of accounting for the spatial effects explicitly. In a parallel vein, Bayesian modeling methods have also been used in this epidemiological context (Gelman et al, 2013;Aswi et al, 2019;Song et al, 2019;Torres-Signes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%